Mixing Religion and Politics: Explaining the South Pacific Countries Stance on the Israeli-Gaza Conflict - Olivia, Yessi (Universitas Cenderawasih, 2025)
On October 26, 2023, United Nations member states cast their votes to adopt a resolution to place an immediate cease-fire between Israel forces and Hamas militants. This call was taken considering that the conflict between the two has caused a significant number of fatalities and has impacted all aspects of life in the Gaza region. Of the 175 countries that voted then, 120 UN member states approved the draft resolution, 45 members abstained, and 14 others were against it. Six of the countries that rejected the resolution were South Pacific countries: Fiji, Papua New Guinea, Micronesia, Nauru, Tonga, and the Marshall Islands. This stance was interesting, considering that one of the rhetorics raised in the concept of the Melanesian Way is anti colonialism. The purpose of this article is to analyze the position of the South Pacific countries in viewing in Gaza based on their UN General Assembly voting behaviors. This paper argues that the position of South Pacific countries regarding the conflict in Gaza is not only influenced by their relations with the United States and Israel but also by the influence of religion in their foreign policymaking. KEYWORDS Foreign Policy; Israel-Palestine Conflict; Melanesian Way; Religion; South Pacific